1983
DOI: 10.1097/00006982-198300330-00019
|View full text |Cite
|
Sign up to set email alerts
|

Macular Oedema and Retinal Branch Vein Occlusion

Abstract: The visual prognosis of patients suffering from retinal branch vein occlusion complicated by macular oedema is assessed in relation to the degress of capillary fallout. Extensive retinal capillary fallout associated with macular oedema was found to confer a poor visual prognosis in a series of 89 patients foNowed for an average time of 14 months. If the degree of capillary fallout associated with marular oedema was minimal, the visual prognosis was considerably improved. The most common cause of reduced centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The most important factor in central visual loss resulting from BRVO is macular edema, which has been reported in 60% of patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important factor in central visual loss resulting from BRVO is macular edema, which has been reported in 60% of patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of triamcinolone acetonide and bevacizumab in the vitreous differ [5,[10][11][12][13] and drug efficacies might thus also be distinct.…”
Section: Introductionmentioning
confidence: 99%
“…Macular edema is the most common cause of vision loss and can be seen in 60% of patients [4]. The only standard treatment for BRVO to date is based on the results of the branch Vein Occlusion Study (BVOS), which suggested that macular photocoagulation of eyes with macular edema should be delayed for at least 3 months to permit maximal spontaneous resolution of the edema and intraretinal blood [1].…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of visual disturbance in BRVO patients is macular edema, which has been reported in 60% of patients [3]. Macular grid laser photocoagulation has been shown to be effective in the treatment of macular edema arising from BRVO [2].…”
Section: Introductionmentioning
confidence: 99%